Potret Kehidupan Suku Togutil dan Kearifan Lokal Khususnya Obat-Obatan Tradisional dari Hutan - Bayau, Edom; Kastanya, Agustinus; Pelupessy, Piter (MAKILA, 2019)
The study was conducted to find a portrait of the life of the Togutil tribe and the use of forest products in the form of medicines that are used as their daily needs. This study used descriptive qualitative method. The purpose of descriptive research is to describe and understand the behavior patterns of a community as it is in the context of wholeness or a unified whole, and the results of the study show that the existence of the Togutil tribe is still highly dependent on the forest. The use of medicines is hereditary knowledge which is still maintained because it is proven by what is directly accepted by the community.